Answer:
Step-by-step explanation:
We have
[tex]f(x) = 6x + 5[/tex]
[tex]g(x) = 3x[/tex]
To find the value of either of these functions for a specific value of x, simply substitute that value into the corresponding function equation.
[tex]\bold{f(2)}[/tex]
Substitute x with 2 in 6x + 5
==> [tex]6\cdot \:2+5=17[/tex] (Answer)
[tex]\bold{g(4)}[/tex]
Substitute x with 4 in g(x) = 3x
==> [tex]3 \cdot4=12[/tex] (Answer)
[tex]\bold{f(-2)}[/tex]
Substitute x with -2 in 6x + 5
[tex]6\left(-2\right)+5=-7[/tex] (Answer)
[tex]\bold{g(0)}[/tex]
Substitute x with 0 in g(x) = 3x
==> [tex]3\cdot0=0[/tex] (Answer)
[tex]\bold{f(\frac{1}{2})}[/tex]
Substitute x with [tex]\frac{1}{2}[/tex] in 6x + 5
==> [tex]6\cdot \frac{1}{2}+5 = 3 + 5 = 8[/tex] (Answer)
[tex]\bold{g(-4)}[/tex]
Substitute x with -4 in g(x) = 3x
==> [tex]3\left(-4\right) = -12[/tex] (Answer)